Negative experiences of Iranian women underwent tubal ligation: A qualitative study - Shahideh Jahanian Sadatmahalleh; Samaneh Youseflu; Saeideh Ziaei; Seyedeh Saeedeh Mousavi (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Tubal ligation (TL) with more than 99% effectiveness considered an irreversible contraceptive method among many couples. Objectives: This study was conducted to identify the challenges and problems of women after tubal ligation (TL) and its physical, psychosocial and familial consequences of this method with a qualitative study. Methods: This descriptive qualitative study was conducted on 14 sterilized women between the ages of 25 and 40 from March to October 2017 in Rasht, Iran. The participants were selected with a purposeful method. Semi-structured interviews were used to collect data. Qualitative data were analyzed using conventional content analysis. Results: The experiences of sterilized women were classified into six main themes: dissatisfaction with sexual and marital life, regret, feelings of resentment and physical-emotional damage, menstrual disorder, feelings of low self-esteem and changes in female identity, disruption of social interactions. Conclusion: Sterilized women experienced a wide range of physical, familial, sexual, and social problems after TL. Therefore, it is necessary to provide effective counseling regarding the positive and negative complications of this method when proposing sterilization.